2016
DOI: 10.1080/19942060.2016.1235515
|View full text |Cite
|
Sign up to set email alerts
|

Active flow control of the vortex rope and pressure pulsations in a swirl generator

Abstract: The vortex rope and pressure pulsations caused by a radial pressure gradient in the conical diffuser of a swirl generator is controlled using continuous slot jets with different momentum fluxes and angles injected from the runner crown. The swirl apparatus is designed to generate flows similar to those in the different operating conditions of a Francis turbine. The study is done with numerical modelling using the hybrid URANS-LES (Unsteady Reynolds-Averaged Navier-Stokes-Large Eddy Simulation) method with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Recent studies of the PVC effect [7][8][9] have focused on developing methods for controlling and suppressing PVC in hydroelectric units, wherein data on the influence of vortex phenomena on the transient turbine are poorly presented in the literature. Transient regimes can occur in regions with a PVC, so it is of considerable interest to study the mechanisms of PVC formation in various transient regimes.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of the PVC effect [7][8][9] have focused on developing methods for controlling and suppressing PVC in hydroelectric units, wherein data on the influence of vortex phenomena on the transient turbine are poorly presented in the literature. Transient regimes can occur in regions with a PVC, so it is of considerable interest to study the mechanisms of PVC formation in various transient regimes.…”
Section: Introductionmentioning
confidence: 99%
“…These active control methods act to increase the axial flux of the moment of momentum to stabilize the flow instead of to diminish the swirl level below the critical level (to decrease the tangential flux of the moment of momentum) like the passive control methods mentioned above. Javadi and Nilsson numerically examined a new idea about the water injection method [29], and considered a swirl component superposed over an axial jet in order to improve its effects. Their investigations have shown that the pressure pulsations, velocity fluctuations and the size of the vortex rope decrease when a jet with a flow rate less than 3% is injected from the runner crown.…”
Section: Introductionmentioning
confidence: 99%
“…The effective development of these technologies is impossible without knowledge of the hydrodynamics of such flows. Such flows also arise in cyclones and draft tubes behind Francis hydraulic turbines in non-optimal operation modes [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%